THE INFLUENCE OF ADOLESCENTS ’ SELF-ESTEEM ON THE MOTIVATION TO ACHIEVE SUCCESS - Magauova, Akmaral; Talipova, Nazym (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article reveals the features of the development of self-esteem and achievement motivation in older adolescents. Adolescence is considered a crisis period in human ontogenesis. In modern studies, there is a steady increase in the formation of unfavorable personality traits in adolescents. At this age, problems with self-esteem of the individual are more common, since the teenager's interest in himself, his self-perception and the need to understand himself are activated by the processes of puberty and psycho-physiological changes. The danger of this tendency for the future generation lies in the fact that inadequate self-esteem can cause the development of insecurity, complexes, anxiety, aggression, and can also act as a factor in suicidal behavior of adolescents. It should be noted that for many years Kazakhstan has been among the ten countries in the world in terms of the number of suicides among adolescents and youth. In modern socio-economic conditions, it is especially important to achieve a high level of development of a teenager's personality, and the formation of such qualities as self-confidence, motivation to achieve success. Therefore, the study of the relationship between self-esteem and the motivation for achieving success of the younger generation, along with modern social and revolutionary changes, is one of the urgent problems. The article presents an analysis of the results of an empirical study, the purpose of which was to identify the relationship between self-esteem and motivation for achieving success in adolescents. To achieve the goal of the study, the following psychodiagnostic methods were used: the method of G.N.Kazantseva "Study of general self-esteem"; the method of A. A. Rean "Motivation for success and fear of failure". The results suggest that there is a close positive relationship between self-esteem and achievement motivation in adolescents